2018
DOI: 10.1177/0731684418777120
|View full text |Cite
|
Sign up to set email alerts
|

Process comparison on the microstructure and mechanical properties of fiber-reinforced polyphenylene sulfide using MuCell technology

Abstract: The MuCell process is a special injection molding process which utilizes supercritical gas (nitrogen) to create integral foam sandwiches. The advantages are lower weight, higher specific properties and shorter cycle times. In this study, a series of glass fiber-reinforced polyphenylene sulfide foam blanks are manufactured using the MuCell injection molding process. The different variations of the process (low-pressure also known as structural foam injection molding) and high-pressure foam injection molding (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, when injection speed is increased from 100 mm/s to 267.8 mm/s, the mean R a decreased from 1.297 µm to 1.072 µm. This reduction in surface roughness with an increase in injection speed can be attributed to the cavity being filled earlier hence the frozen layer may have started to freeze thus mitigating the polymer/gas solution from reaching the moulding surface [43,44]. When processing with a higher melt temperature, the R a decreased from 1.324 µm to 1.045 µm.…”
Section: Part Surface Roughnessmentioning
confidence: 99%
“…Furthermore, when injection speed is increased from 100 mm/s to 267.8 mm/s, the mean R a decreased from 1.297 µm to 1.072 µm. This reduction in surface roughness with an increase in injection speed can be attributed to the cavity being filled earlier hence the frozen layer may have started to freeze thus mitigating the polymer/gas solution from reaching the moulding surface [43,44]. When processing with a higher melt temperature, the R a decreased from 1.324 µm to 1.045 µm.…”
Section: Part Surface Roughnessmentioning
confidence: 99%
“…Moreover, the use of MuCell ® to produce lightweight parts for automotive and aerospace applications reduces fuel consumption and contributes to reduce CO2 emissions [9][10][11]. However, the light weight can lead to poor mechanical properties, and consequently several authors investigated strategies to improve mechanical properties of MuCell ® parts [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A non-linear impact of mould temperature and cell size was also reported, with results indicating that by increasing the mould temperature, the cell size initially decreases and then increases [ 33 ]. Contrarily, Lohr et al [ 34 ] found that the influence of the injection velocity can be neglected. Liu et al [ 35 ] concluded that the cell density decreases in a linear way by decreasing the shot volume and that the effect of gas content on the cell density can be neglected.…”
Section: Introductionmentioning
confidence: 99%